The nature of strategic group conversations: orientations, functions and intertextuality in a single case setting - Moore, S. (Cranfield University, 1997)
This thesis sets out to develop and apply a framework for the analysis of strategic group conversations. Through an exploration of existing research and literature in the areas of conversation and strategy, four key levels of analysis are used for evaluating and comparing different dimensions of one stream of strategic conversations. Most particularly, the comparison between written and spoken dimensions of the conversations is carried out leading to several findings which throw new light on some central dimensions of strategic conversations. It is suggested that the methodology developed here, and the subsequent findings might usefully be compared in other case settings. Key findings from the research include the following: A present time orientation is more likely to be adopted than that of a future time orientation in spoken dimensions of strategic conversation. In contrast, a future time orientation predominates in written dimensions of the conversation. The present is spoken of in significantly more ‘context rich’ terms than the future, whereas the written dimension reveals that future contextual issues receive significantly more attention than do current contextual issues. Advice produced by strategic conversations (both written and spoken) tends to be structural rather than behavioural and contextual introversion predominates in both written and spoken communication. Written communication in this case setting has been found to exaggerate the generalised focus of spoken references to the organisation. It has also been found to exaggerate the particularised focus of spoken references to the strategic initiative. A model outlining key aspects of the nature of strategic conversations is also presented showing that both explicit and implicit functions can be identified using a structured approach to analysing strategic conversations. Finally, perceived moderators and emerging norms are also shown to be discoverable through the structured qualitative analysis outlined in this research.